2008
DOI: 10.1097/gim.0b013e31817701c1
|View full text |Cite
|
Sign up to set email alerts
|

The beliefs, and reported and intended behaviors of unaffected men in response to their family history of prostate cancer

Abstract: Participants commonly believed behavioral factors influenced prostate cancer risk and reported that they would alter their behavior to reduce risk after (hypothetical) genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…Nine studies were conducted in the USA; 185,186,189,192,[194][195][196][197]199 one of these was colocated in Puerto Rico; 185 five were conducted in the UK, [167][168][169][170][171] three in Australia, 190,193,198 two in Canada 187,188 and one in Germany. 191 Thirteen studies evaluated adults' views concerning the taking of vitamins and minerals, 169,185,187,[189][190][191][192][193][195][196][197][198][199] five studies considered aspirin or NSAIDs, [168][169][170][171]194 two folic acid 167,185 and two dietary supplements generally. 186,188 Only four studies explored the views of participants who had either a cancer diagnosis 186,197,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies were conducted in the USA; 185,186,189,192,[194][195][196][197]199 one of these was colocated in Puerto Rico; 185 five were conducted in the UK, [167][168][169][170][171] three in Australia, 190,193,198 two in Canada 187,188 and one in Germany. 191 Thirteen studies evaluated adults' views concerning the taking of vitamins and minerals, 169,185,187,[189][190][191][192][193][195][196][197][198][199] five studies considered aspirin or NSAIDs, [168][169][170][171]194 two folic acid 167,185 and two dietary supplements generally. 186,188 Only four studies explored the views of participants who had either a cancer diagnosis 186,197,…”
Section: Resultsmentioning
confidence: 99%
“…[185][186][187][188][189][190][191][192][193][194] Five further studies were identified by unstructured searching. [195][196][197][198][199] In total, 20 studies were included. For details of the search and selection process, see the flow diagram of studies ( Figure 12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this would be successful only if patients were willing to trust negative screen results, given a prevailing culture that seems to promote higher levels of screening as "better" screening practice. [75][76][77] Thus, SNP-based screening panels need to demonstrate increased specificity, and may also need to demonstrate superior levels of sensitivity, compared with PSA-based screening for patients and their physicians to have confidence in their use, especially in view of the debate about PSA-based screening. 18,[78][79][80] Some studies have suggested that the use of SNP-based models in stratifying PSA thresholds could improve PSA-based screening.…”
Section: Discussionmentioning
confidence: 99%